MEMPERTAHANKAN OTORITAS ALKITAB DI ERA POSTMODERN: KRITIK RELATIVISME DAN TAWARAN HERMENEUTIKA KONTEKSTUAL - Koanak, Ivoni Arisandi Kristina; Sanda, Hendrik Yufengkri (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
In the postmodern era, views on the Bible are challenged by changes in cultural paradigms, philosophy, and the way people think. Traditionally, the Bible, which is considered an authoritative and absolute source, is often questioned or reinterpreted based on the framework of individual subjectivity. Postmodernism shifts the focus from objective understanding to personal and subjective interpretation. Postmodernists see the Bible as a cultural narrative that is open to various interpretations, without recognizing a single truth. A more narrative and relational approach, as well as recognition of plurality of views, can be used to reach individuals who feel alienated by an overly dogmatic approach. The method used in this study is qualitative research with a descriptive-analytical approach. The results of the study show that the views of postmodernists are wrong because they are built on the principles of subjectivism, pluralism, relativism and skepticism. The Bible in the postmodern world requires an adaptive approach but still adheres to solid theological principles. The church and Christian communities must continue to explore creative ways to explain the relevance of the Bible as the living word of God in a changing culture.